Mıttıgatıon Of Power Losses In Transmıssıon Lıne - Manish Shrivastava, Gaurav Rajput, Ashish Kumar, Manish Kumar, Manoj Kumar Yadav (International Journal of Advanced Science and Technology, 2020)
This division inspects the efficiency of the UPFC in modifiable electricity flow. This study works with numerical simulations of the predictable IEEE 39 bus system with UPFC, and launches three data simulations to recover real and reactive power management over the diffusion line through the device. Deprived of installation of device UPFC, the real and reactive power cannot be controlled across the power line. Project model for UPFC device was evolved using rectifiers & inverter circuits. MATLAB  results are presented to authenticate the model. The output of the network is added to UPFC and cannot be used to study UPFC activity by matching active and reactive current lines on the line, current and reactive currents on the bus.